From Prestige to Humanism: The Experiences of Medical Students about Motivational Factors - Majid Khadem Rezaiyan; Alireza Omranzadeh; Arash Akhavan Rezayat; Masoud Youssefi (Zanjan University of Medical Sciences and Health Services, 2019)
Background & Objective: Students are invaluable assets of every country. Medicine has long been a major of great interest worldwide, the selection of which involves numerous motivational factors. The present study aimed to assess various motivational factors in medical students since the first until the last year of education. Materials and Methods: This cross-sectional study was conducted on the medical students at Mashhad University of Medical Sciences in Mashhad, Iran in 2016. In total, 200 students were selected via stratified cluster sampling. Data were collected using a researcher-made questionnaire with 29 items regarding motivational factors. The questionnaire was validated (α=0.77) and completed by the participants. Results: The main reasons for the selection of medicine as a field of studies were as follows: "Doctors have a good social status." (n=84; 46.7%), "I wanted to help people improve their health." (n=81; 44.8%), and "I wanted to be self-employed in the future." (n=73; 40.8%). The male students were more concerned about financial income (mean score: 1.1±0.7 vs. 0.8±0.9; P=0.04) and job security (mean score: 0.4±1.1 vs. 0.1±1; P=0.05) compared to the female students. Moreover, the viewpoint of the students toward the propriety of the duration of medical education completely changed (0.7 in basic sciences up to -0.4 in internship; P<0.001). Conclusion: According to the results, some motivational factors varied significantly as the medical students progressed into educational stages, which could be explained by the fact that medical students became more realistic than idealistic as they started actual medical practice during clinical education.